2008
DOI: 10.1037/1064-1297.16.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Simulated driving performance of adults with ADHD: Comparisons with alcohol intoxication.

Abstract: Previous research has demonstrated that adults with ADHD are more likely to experience drivingrelated problems, which suggests that they may exhibit poorer driving performance. However, direct experimental evidence of this hypothesis is limited. The current study involved two experiments that evaluated driving performance in adults with ADHD in terms of the types of driving decrements typically associated with alcohol intoxication. Experiment 1 compared the simulated driving performance of 15 adults with ADHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 54 publications
2
56
0
2
Order By: Relevance
“…The results showed that sober adults with ADHD were comparable to intoxicated controls with regard to lane deviation, fast/abrupt steering maneuvers, and speed variability. In addition, alcohol consumption was shown to further compromise the attention and driving performance of adults with ADHD [21,22]. These findings are further supported by data showing greater disinhibitory effects of alcohol on adults with (n=10) versus without (n=12) ADHD on a cued go/no-go task [23•].…”
Section: Laboratory Findings That Distinguish Drivers With Attention-mentioning
confidence: 75%
See 1 more Smart Citation
“…The results showed that sober adults with ADHD were comparable to intoxicated controls with regard to lane deviation, fast/abrupt steering maneuvers, and speed variability. In addition, alcohol consumption was shown to further compromise the attention and driving performance of adults with ADHD [21,22]. These findings are further supported by data showing greater disinhibitory effects of alcohol on adults with (n=10) versus without (n=12) ADHD on a cued go/no-go task [23•].…”
Section: Laboratory Findings That Distinguish Drivers With Attention-mentioning
confidence: 75%
“…In 2010, Reimer et al [20•] compared 60 drivers (25 young adults with, 35 without ADHD) while they manipulated boredom or challenge of the drive and concluded that drivers with ADHD appeared to be particularly susceptible to distraction during periods of low-stimulus driving. Weafer et al [21] compared the driving performance of sober and intoxicated ADHD (n= 15) and non-ADHD adults (n=23 adults) (alcohol dose, 0.65 g/kg). The results showed that sober adults with ADHD were comparable to intoxicated controls with regard to lane deviation, fast/abrupt steering maneuvers, and speed variability.…”
Section: Laboratory Findings That Distinguish Drivers With Attention-mentioning
confidence: 99%
“…As discussed above, we have demonstrated significantly worse driving performance in adults with ADHD relative to controls under both a moderate and high dose of alcohol in our lab (Weafer et al, 2008). In fact, on some driving measures, those with ADHD displayed significant impairment relative to placebo in response to the moderate dose of alcohol, which produced mean BACs around .05% (well under the legal limit of intoxication).…”
Section: Implications and Potential Risk Management Strategiesmentioning
confidence: 80%
“…The cognitive deficits present in those with the disorder set the stage for potentially seriously impaired driving performance, and for this reason it is imperative that researchers, clinicians, and individuals with the disorder (and those close to them) learn as much as possible about the dangers and ways in which they can be prevented. Here, we wish to summarize research findings from an article we recently published in the journal Experimental and Clinical Psychopharmacology and highlight several policy implications (Weafer, Camarillo, Fillmore, Milich, & Marczinski, 2008).…”
Section: Jessica Weafer Richard Milich and Mark T Fillmorementioning
confidence: 99%
See 1 more Smart Citation